DUNIA CYBERSPACE BAUDRILLARDIAN â€œTHE MATRIXâ€ - Baktiono, Wolly (Scriptura, 2008)
Baudrillard, following Barthes, noted the movements which easily altered to visual experience where driver or viewer interacted with image, than with physical world (Ecstasy 13). Other than metaphorical transformation from physical world to image â€œonâ€ a windshield, â€œcyberspaceâ€ provides simulations behind monitor screen. Whatâ€™s real will no longer as a reference for postmodern version of Window Alberti. Scene or simulation screen is a shallow surface that no longer conforms to image games between metaphor and the represented world. For Baudrillard, screen provides the example of â€œreality satelitationâ€ reaching speeds detachment and hyperreality. â€œIt once to be previously mentally projected that lives as a metaphor in terrestrial habitat which from now on projected entirely without metaphor, into definite space of simulationâ€ (Ecstasy 16). Not for long now the metaphor to change, simulated highway of Internet as a form of virtual reality. Virtual reality doesnâ€™t mean â€œrepresentation of realityâ€ but a â€œsimulation of realityâ€. Baudrillard explained that simulation is the creation of reality models which without origin or without reality, but hyperreal! People believed the already constructed reality, as social construction of reality (adopted from the concept of Peter L. Berger and Thomas Luckman), like drama scenario, which define individual roles, change the narration, build its self image and collectively and oddly includes exploring the cyberspace. Computer technology, internet, virtual reality, artificial intelligence and cyberspace, has loaded with pseudo-event, which eventually offers virtual community.